Pengaruh Aplikasi Power Point Terhadap Hasil Belajar Peserta Didik Kelas X TKJ di SMK Negeri 1 Raren Batuah: The Influence of the Power Point Application on the Learning Outcomes of Class X TKJ Students at SMK Negeri 1 Raren Batuah - Muhammad Akbar; Hendri Hendri; Muhammad Jailani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The objectives of this study were to: (1) determine the effect of the power point application on the learning outcomes of class X TKJ students on the subject of PC assembly at SMKN 1 Raren Batuah (2) find out the differences in student learning outcomes in class X TKJ SMKN 1 Raren Batuah between pre -test with Post-test. The population of this research is all students of class X TKJ (computer and network engineering) SMKN 1 Raren Batuah, Raren Batuah sub-district, East Barito Regency, Central Kalimantan province. A total of 30 students. The sample of this study was the entire population of class X TKJ SMKN 1 Raren Batuah students who received different treatments in a certain period. The results showed that: (1) the use of power point applications, affected the learning outcomes of students of class X TKJ experienced an increase in the ability to answer multiple choice questions (2), the learning outcomes of students of class X TKJ who did not use power point applications (pre- test) got an average of 69.07 < compared to the use of the power point application, the average learning outcomes of X TKJ students in the PC assembly subject at SMKN 1 Raren Batuah was 76.63. Broadly speaking, it can be stated that there is a positive influence on student learning outcomes during the use of the power point application